Carbon-rich materials with three-dimensional ordering at the angstrom level. Issue 23 (5th June 2020) - Fa, Shixin; Yamamoto, Masanori; Nishihara, Hirotomo; Sakamoto, Ryota; Kamiya, Kazuhide; Nishina, Yuta; Ogoshi, Tomoki
Abstract : We discuss the preparation and application of various carbon-rich materials with three-dimensional ordering at the angstrom level. Abstract : Carbon-rich materials, which contain over 90% carbon, have been mainly synthesized by the carbonization of organic compounds. However, in many cases, their original molecular and ordered structures are decomposed by the carbonization process, which results in a failure to retain their original three-dimensional (3D) ordering at the angstrom level. Recently, we successfully produced carbon-rich materials that are able to retain their 3D ordering at the angstrom level even after the calcination of organic porous pillar[6]arene supramolecular assemblies and cyclic porphyrin dimer assemblies. Other new pathways to prepare carbon-rich materials with 3D ordering at the angstrom level are the controlled polymerization of designed monomers and redox reaction of graph. Electrocatalytic application using these materials is described.